2002
DOI: 10.1161/01.cir.0000015505.24187.fa
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and Biochemical Markers of Human Fetal Cardiac Dysfunction in Placental Insufficiency

Abstract: Background-Placental insufficiency may lead to fetal cardiovascular compromise. We sought to determine whether ultrasonographic parameters of fetal cardiovascular function correlate with umbilical arterial levels of biochemical markers of myocardial dysfunction and damage in placental insufficiency. Methods and Results-In 48 fetuses with placental insufficiency, umbilical artery blood was obtained at delivery for assessment of N-terminal peptide of proatrial natriuretic peptide (NT-proANP) and cardiac troponin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
1
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 35 publications
8
106
1
7
Order By: Relevance
“…The CVP score includes fetal sonographic markers that have been correlated with poor perinatal outcome 14,15 . These markers were chosen for inclusion in the score because they combine mechanisms 16 by which the fetal circulation could fail in normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CVP score includes fetal sonographic markers that have been correlated with poor perinatal outcome 14,15 . These markers were chosen for inclusion in the score because they combine mechanisms 16 by which the fetal circulation could fail in normal sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on growth-restricted fetuses have also suggested that abnormalities in fetal venous circulation are important indicators for the optimal timing of delivery 3,5,18 . Increased pulsatility in fetal systemic venous blood velocity waveforms is related to a rise in systemic venous pressure 19 , reflecting both ventricular compliance and ventricular end-diastolic pressure, and it has also been associated with biochemical evidence of cardiac dysfunction 15 . Tricuspid valve regurgitation reflects changes in right ventricular loading conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 In the present study, PIV in the ductus venosus was increased, suggesting a rise in systemic venous pressure. 34 Within 6 hours, 3 of the 26 fetuses in the LPS group were dead. Approximately 65% of the surviving fetuses had valve regurgitations present after LPS administration.…”
Section: Discussionmentioning
confidence: 99%
“…Prepartum evaluation of the pulsatility in fetal systemic veins significantly correlated to the cardiac secretion of ANP. Fetal myocardial compromise resulted in a distribution of cardiac output toward the left ventricle and a rise in the right-ventricular afterload, explaining the increase in ANP (38). Seong et al, in a study to evaluate the relationship between NT-proBNP levels and the method of delivery, found that infants with low Apgar scores and low umbilical cord blood pH appeared to have increased levels of NT-proBNP (18).…”
Section: Clinical Indicationsmentioning
confidence: 99%